Analisis Keuntungan Usaha Minuman Herbal Eufrain Pada UD Makaaruien Di Kecamatan Malalayang Kota Manado - Lamunde, Mario Aditya Fernanda Kalvari; Jocom, Sherly G.; Wariki, Barce A.F. (Sam Ratulangi University, 2024)
The aim of this research is to determine the extent of profit received by the company from the sales of the Eufraino product at UD Makaaruien in Manado City within one production month. This research was conducted over two months, from June to July 2023, at UD Makaaruien in Malalayang District, Manado City. The research method used is a case study at UD Makaaruien in Manado City. Data collection was performed using primary data obtained directly through interviews with the owner of UD Makaaruien using a prepared questionnaire. The data collected in this study were analyzed using profit analysis, which involves calculating the difference between revenue and costs incurred. The collected data are presented in table form and explained descriptively. The results show that the Eufraino product business at UD Makaaruien in Malalayang District, Manado City, is profitable. UD Makaaruien incurred an average cost of IDR3,129,829 per production month, with an average revenue of IDR5,129,000 per production month, resulting in an average profit of IDR1,999,171.